Implementasi Pendekatan Contextual Teaching Learning dalam Mendukung Critical Thinking Skills Peserta Didik pada Mata Pelajaran IPAS - Ramadhanti, Tasya Putri; Yandari, Indhira Asih Vivi; Hakim, Zerri Rahman (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study was to describe the planning of educators, the learning process and the results of the implementation of the CTL approach in the subject of science in supporting critical thinking skills of grade IV students. This study uses a qualitative approach with a descriptive method. Data collection was carried out through interviews, observations and documentation, with the principal, educators, and students, as well as conducting a literature review. The results obtained in this study are that the planning of science learning is carried out by determining CP, TP & ATP, and compiling teaching modules that are in accordance with the characteristics of the material being studied. The learning process runs conducively, is centered on students and involves students to play an active role. Based on the results of the study, the CTL approach to science learning is able to support the development of critical thinking skills of grade IV students.